Perlindungan Hukum terhadap Data Pribadi Pengguna Jasa Transportasi Online - I Gusti Dama Galang Devara; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
Technological developments have brought an impact on all community activities, one of which is the emersion of online transportation services such as those provided by Gojek, Grab, Uber, and others which do not only provide the services of riding but also the services of the delivery of goods, food and others. Using online transportation services requires users to download the application and register themselves. However, the personal data of the service users are often misused by drivers for certain reasons and purposes. To overcome and anticipate this, a strict legal regulation appearing as the legal umbrella to protect each online transportation user from misuse of their personal data by the driver is necessary. This study examines the forms of legal protection for users of online transportation services. Conducted in the design of normative legal research, the study makes use of articles and paragraphs of the laws on transportation and several other related laws. The results of the study indicate that legal protection for users of online transportation services from misuse of their personal data takes the form of repressive legal protection. Online transportation service users are permitted to file a civil suit to the online transportation service provider and to file a direct criminal suit regarding the acts of the driver, not on behalf of the online transportation service provider. Efforts to resolve the dispute-causing acts of misuse of personal data of online transportation service users can be made through deliberations, arbitration and courts. The three forms of settlement are in accordance with Article 45 Paragraph (1), (2) of the Indonesian Basic Agrarian Law and Article 6 of the Arbitration Law. Regarding the act of arbitrary canceling the use of online transportation services by service users appears a crucially urgent object to be studied from a legal perspective in the next studies.